Gas Permeability Prediction of Mortar Samples Based on Different Methods - Zirui Cheng; Yiren Wang; Jihui Zhao; Chunlong Huang (Crystals, 2022)
Gas permeability is one of the durability indicators of cementitious materials; permeability predictions based on pore characteristics are useful approaches to obtain gas permeability when experimental conditions are limited. In this study, the gas permeabilities of mortar are predicted by using the Hagen–Poiseuille equation combined with a processed backscattered electron (BSE) image, the Katz–Thompson equation, and the Winland model with pore parameters obtained from MIP tests. The permeabilities calculated by the BSE method are different from the measured value because the observation range is limited and it is difficult to completely display the actual pore structure. The Katz–Thompson equation underestimates the contribution of coarse capillary pores on permeability, thus the results are two orders of magnitude lower than the measured value. The results obtained from the Winland model are close to the measured permeabilities, which indicate that the Winland model is the most suitable method for predicting gas permeability among the three methods described in this paper.